2022
DOI: 10.4103/atm.atm_191_21
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and mental health in coronavirus disease 2019 patients and general population during the pandemic

Abstract: OBJECTIVE: Sleep problems during the coronavirus disease 2019 (COVID-19) pandemic commonly affected general populations. Data on the effect of the COVID-19 pandemic on sleep quality in Saudi Arabia are scarce. Thus, the aim of our study was to evaluate sleep quality and assess the psychological burden of the pandemic in COVID-19 patients and the general population. METHODS: This was a multicenter, observational, cross-sectional survey. Participants with COVID-19 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The prevalence of insomnia, anxiety, depression and obesity increased with increasing phone screen time among university students. Of all countries, Iran reported the highest prevalence of insomnia among adults (55.2%) 46 53. Finally, in a Turkey-based study among pregnant women, mild sleepiness was found in 88.2% of participants (n=356), while severe sleepiness was reported in 11.8% of the same sample 54…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The prevalence of insomnia, anxiety, depression and obesity increased with increasing phone screen time among university students. Of all countries, Iran reported the highest prevalence of insomnia among adults (55.2%) 46 53. Finally, in a Turkey-based study among pregnant women, mild sleepiness was found in 88.2% of participants (n=356), while severe sleepiness was reported in 11.8% of the same sample 54…”
Section: Resultsmentioning
confidence: 95%
“…SQ was altered for both COVID-19 patients and healthy individuals 46. The Pittsburgh Sleep Quality Index (PSQI) score during lockdown was predominantly influenced by sleep-onset latency, sleep efficiency and total sleep time 47.…”
Section: Resultsmentioning
confidence: 99%
“…During the past years, prevalence studies of poor sleep quality in COVID-19 patients found wide variations, ranging from 25.5 to 88.6% (12)(13)(14), which is probably related to differences in COVID-19 severity and stages (e.g., COVID-19 onset, recovery, acute postsymptom onset), comorbidities, treatment regimens, and measures on sleep quality and cut-off values (15)(16)(17)(18)(19). There are various systematic reviews and meta-analyses that focused on the management of COVID-19, such as the role of methylprednisolone (20), aspirin (21), and baricitinib (22) in COVID-19 patients, but no meta-analysis on the prevalence of poor sleep quality in COVID-19 patients has been published.…”
Section: Introductionmentioning
confidence: 99%
“…Depression was found to be one of the most common and prominent psychological symptoms during this period ( 8 ). Almost half of the adult participants reported depressive symptoms during the lockdown ( 9 ), and the prevalence of depression in the general population (70.10%) was significantly higher compared with COVID-19 patients (39.50%) ( 10 ).…”
Section: Introductionmentioning
confidence: 99%